Preparation method of high-transparency hydrophobic glass

By using alkaline etching liquid and inorganic salts on the glass surface to form nanostructures and coating low-surface energy substances, the problems of decreased transmittance and environmental pollution in the existing high-hydrophobic glass preparation methods are solved, and high transparency, high hydrophobic, low pollution and low cost are achieved.

CN119859025APending Publication Date: 2025-04-22HANGZHOU HIKVISION DIGITAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510088071.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing high-hydrophobic glass preparation methods have problems such as decreased transmittance, expensive equipment, complex processes and environmental pollution, and it is difficult to achieve both high transparency, high hydrophobic, low pollution and low cost.

Method used

An alkaline etching liquid and inorganic salt are used to form nanostructures on the glass surface and coat them with low surface energy substances. These technical methods are combined to prepare highly transparent hydrophobic glass.

Benefits of technology

The high transmittance and high hydrophobicity of glass are achieved, while avoiding the use of highly corrosive acids and high-cost equipment, reducing process complexity and environmental pollution, and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859025A_ABST
    Figure CN119859025A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-transparency hydrophobic glass. The preparation method comprises the following steps: etching a micro-nano structure on the surface of glass by adopting an alkaline etching solution; inorganic salt is adopted to treat the micro-nano structure at 500-600 DEG C, and a nano structure is obtained; and coating a low-surface-energy substance on the nano structure to obtain the high-transparency hydrophobic glass. The method can improve the transmittance of the glass on the basis of keeping the hydrophobicity of the glass, and has the advantages of simple process, low cost and low pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transparent hydrophobic materials, and in particular to a method for preparing highly transparent hydrophobic glass. Background Art

[0002] The surface wettability of a material is an important physical and chemical property of the material, which affects the friction, adhesion, adsorption and other performances of the solid surface. Generally, a surface with a water contact angle greater than 90° is a hydrophobic surface. Hydrophobic surfaces are widely used in self-cleaning, anti-fog, anti-icing, antibacterial and other fields.

[0003] Theory and practice have proven that coating the glass surface with low surface energy materials can make the glass surface present a larger water contact angle (100°~120°) and oil contact angle (60°~65°). However, even if the material with the lowest surface energy is used for modification, the maximum water contact angle on the smooth surface can only reach 120°. In order to further increase the hydrophobicity of the glass surface, the roughness of the glass surface can also be changed. However, changing the roughness of the glass often leads to a decrease in the transmittance of the glass, which is not good for solid surfaces in certain special fields, such as camera windshields, eyeglass lenses or screen protectors.

[0004] CN107500554A discloses a super-hydrophobic transparent glass and a preparation method thereof, comprising the following steps: using an ultrashort pulse laser to carve a micro-nano structure on the surface of ordinary glass or quartz glass, and then hydrophobizing the etched glass surface with fluorosilane or oxygen silane. Although the water contact angle of the glass surface prepared by this method can reach 160°, the visible light transmittance of the glass will decrease by 1%-2% compared with the untreated glass, and the maximum transmittance can only reach 92%, and the equipment used in this method is expensive, which greatly increases the preparation cost.

[0005] CN107365088A discloses a method for preparing a super-hydrophobic film on a glass surface, comprising the following steps: applying a gel film on the glass surface by a sol-gel process, then treating the glass surface with an acid-etching solution to obtain a porous film, and finally applying a low-surface-energy substance on the porous film to obtain a super-hydrophobic film. Although the coating transmittance prepared by the method can reach 94% and the water contact angle reaches 151°, highly corrosive acids such as hydrofluoric acid and nitric acid are used in the preparation process, which is not only environmentally unfriendly, but also increases safety hazards.

[0006] Therefore, there is an urgent need to develop a method for preparing highly hydrophobic glass with high transmittance, low environmental pollution, simple process flow, safety and low cost. Summary of the invention

[0007] In view of the above-mentioned defects, the present invention provides a method for preparing highly transparent hydrophobic glass. The method combines alkaline etching solution and molten salt to form a nanostructure on the glass surface, and then combines it with low surface energy substances, so that the glass has high transmittance and high hydrophobicity. The process is safe and has the advantages of low pollution and low cost.

[0008] The present invention provides a method for preparing highly transparent hydrophobic glass, comprising the following steps:

[0009] (1) Etching micro-nano structures on the glass surface using alkaline etching solution;

[0010] (2) treating the micro-nano structure at 500-600° C. with an inorganic salt to obtain a nanostructure;

[0011] (3) Coating a low surface energy material on the nanostructure to obtain a highly transparent hydrophobic glass.

[0012] In one embodiment of the present invention, taking the number of atoms of silicon, oxygen, sodium, aluminum, potassium, tin, magnesium and calcium as the total atomic amount, in the micro-nano structure, the atomic percentage of magnesium in the total atomic amount is 0.1-0.2%, and the atomic percentage of calcium in the total atomic amount is 0.1-0.3%.

[0013] In one embodiment of the present invention, the alkaline etching solution comprises: 3 to 7 parts by weight of alkali, 0.5 to 1.5 parts by weight of an ion chelating agent, 0.2 to 0.5 parts by weight of aluminate, and 80 to 120 parts by weight of deionized water.

[0014] In one embodiment of the present invention, the base includes one or more of sodium bicarbonate, sodium triphosphate, sodium hydroxide, potassium hydroxide, ammonia water, sodium pyrophosphate, and sodium carbonate.

[0015] In one embodiment of the present invention, the ion chelating agent includes one or more of ethylenediaminetetraacetic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylphosphonic acid, and ethylenediaminetetramethylenephosphonic acid.

[0016] In one embodiment of the present invention, the aluminate comprises sodium aluminate and / or potassium aluminate.

[0017] In one embodiment of the present invention, the weight percentage of the aluminate to the alkali is less than or equal to 10%.

[0018] In one embodiment of the present invention, the step (1) specifically comprises:

[0019] Immersing the glass in the alkaline etching solution, etching at 80-100° C. for 10-28 hours, with the glass being perpendicular to the bottom of the etching reaction device;

[0020] And / or, the step (2) specifically comprises: spreading the inorganic salt evenly on the micro-nano structure, and treating at 500-600° C. for 1-3 hours.

[0021] In one embodiment of the present invention, the molten salt comprises nitrate and chloride;

[0022] Preferably, the weight ratio of the nitrate to the chloride is 1:1;

[0023] Preferably, the nitrate comprises potassium nitrate and / or sodium nitrate, and the chloride comprises sodium chloride and / or potassium chloride.

[0024] In one embodiment of the present invention, the low surface energy material comprises one or more of perfluoropolyether siloxane, fluorosilane and oligosiloxane;

[0025] And / or, the glass is soda-lime glass.

[0026] The present invention uses alkaline etching solution and molten salt to treat the glass surface to obtain a nanostructure, and at the same time coats a low surface energy substance on the nanostructure, so that the glass has high transmittance and high hydrophobicity. In addition, no highly corrosive acid and high-cost equipment are used in the reaction process, so the glass is environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of water contact angle;

[0028] Figure 2 is a schematic diagram of the rolling angle;

[0029] Figure 3 This is a SEM image of the untreated soda-lime glass surface in an embodiment of the present invention;

[0030] Figure 4 is a SEM image of the surface of the soda-lime glass after etching in Example 1 of the present invention;

[0031] Figure 5 This is a SEM image of the surface of the soda-lime glass after etching and inorganic salt treatment in Example 1 of the present invention;

[0032] Figure 6 : EDS images of elements of the cross section of the soda-lime glass after etching in Example 1 of the present invention, wherein (a) is a SEM image of the cross section of the soda-lime glass, (b) is an EDS image of the Ca element on the surface of the soda-lime glass, (c) is an EDS image of the Mg element on the surface of the soda-lime glass, and (d) is an EDS image of the Al element on the surface of the soda-lime glass;

[0033] Figure 7The transmittance of the glass (hydrophobic glass) and the untreated soda-lime glass (white glass) prepared in Example 1 of the present invention;

[0034] Figure 8 The water contact angle of the glass prepared in Example 1 of the present invention;

[0035] Fig. 9 This is a picture of the glass prepared in Example 1 of the present invention after being subjected to a water spray test. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] For ease of understanding, the relevant technologies involved in the present invention are first introduced below.

[0038] 1. Hydrophobic

[0039] A surface with a water contact angle greater than 90° is a hydrophobic surface; if the water contact angle is greater than 150° and the sliding angle is less than 10°, it can be called a superhydrophobic surface.

[0040] 2. Water contact angle

[0041] Refers to the angle between the solid-liquid interface, the liquid interior and the gas-liquid interface at the interface of solid, liquid and gas. Figure 1 As shown, θ c is a graphic representation of the water contact angle.

[0042] 3. Roll Angle

[0043] When the droplet just rolls on the inclined surface, the critical angle formed by the inclined surface and the horizontal plane is represented by α, as shown in Figure 2 shown.

[0044] The present invention provides a method for preparing highly transparent hydrophobic glass, comprising the following steps:

[0045] (1) Etching micro-nano structures on the glass surface using alkaline etching solution;

[0046] (2) using inorganic salts to treat the micro-nanostructure at 500-600°C to obtain a nanostructure;

[0047] (3) Coating low surface energy materials onto the nanostructures to obtain highly transparent hydrophobic glass.

[0048] Before executing the method of the present invention, the glass may be pretreated. The present invention does not specifically limit the pretreatment method. For example, the glass surface may be cleaned with an ethanol solution and then dried. The present invention does not limit the concentration of ethanol and the drying temperature. For example, the volume concentration of ethanol in the ethanol solution may be 75% or 65%.

[0049] The present invention does not limit the use of the glass. For example, the glass of the present invention can be used as a camera windshield, eyeglasses, or screen protection glass.

[0050] In a specific embodiment, the atomic number of silicon (Si), oxygen (O), sodium (Na), aluminum (Al), potassium (K), tin (Sn), magnesium (Mg) and calcium (Ca) is the total atomic number. In the micro-nano structure etched by step (1), the atomic percentage of Mg in the total atomic number is 0.1-0.2%, and the atomic percentage of Ca in the total atomic number is 0.1-0.3%. On the unetched glass surface, the atomic percentage of Mg in the total atomic number is 2.6%, and the atomic percentage of Ca in the total atomic number is 3.6%. Compared with the unetched glass surface, the Mg and Ca elements on the glass surface after etching are reduced. The change in the element density of the etching layer may bring about a change in the refractive index of the etching layer, thereby reducing the reflectivity of light at the air / glass interface. Since the transmittance of glass = 1-reflectivity-absorption, the change in the element density of the etching layer can improve the transmittance of glass.

[0051] It should be noted that, since the inorganic salt treatment does not belong to a chemical reaction, the atomic percentage in the micro-nano structure can be used to represent the atomic percentage in the nanostructure.

[0052] The atomic percentage of each element in the micro-nanostructure can be tested by energy dispersive spectroscopy (EDS).

[0053] In a specific embodiment, the alkaline etching solution includes: 3 to 7 parts by weight of alkali, 0.5 to 1.5 parts by weight of ion chelating agent, 0.2 to 0.5 parts by weight of aluminate, and 80 to 120 parts by weight of deionized water. For example, the alkaline etching solution includes 3 parts by weight of alkali, 0.5 parts by weight of ion chelating agent, 0.2 parts by weight of aluminate, and 80 parts by weight of deionized water, or the alkaline etching solution includes 3 to 7 parts by weight of alkali, 1.5 parts by weight of ion chelating agent, 0.5 parts by weight of aluminate, and 120 parts by weight of deionized water, or the alkaline etching solution includes 5 parts by weight of alkali, 1 part by weight of ion chelating agent, 0.4 parts by weight of aluminate, and 100 parts by weight of deionized water.

[0054] When the alkaline etching solution adopts the above components, the alkali can open the Si-O-Si skeleton in the glass structure through free hydroxide, so that the Na + , Ca 2+ , K + Mg 2+ Cations can escape from the Si-O-Si framework of the glass; ion chelators can capture the escaped monovalent and divalent cations and accelerate the etching reaction; aluminates can not only provide hydroxide ions, but also react with free Al in the glass after the Si-O-Si framework of the glass is opened. 3+ Double hydrolysis reaction occurs, namely Al 3+ +3AlO 2- +6H 2 O=4Al(OH) 3 ↓, which can further accelerate the etching reaction. When the proportion of the components in the alkaline etching solution is within the above range, the various combinations can cooperate with each other to etch a micro-nano structure on the glass surface, thereby improving the surface roughness and porosity of the glass.

[0055] The present invention does not impose any particular limitation on the sources of the alkali, ion chelating agent, aluminate and deionized water. For example, they can be purchased from commercial products or prepared by conventional methods.

[0056] In one embodiment, the base comprises sodium bicarbonate (NaHCO 3 ), sodium triphosphate (Na 3 PO 4 ), sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonia (NH 3 ∙H 2 O), sodium pyrophosphate (Na 4 P 2 O 7 )、Sodium carbonate(Na 2 CO 3 When the above substances are used, sufficient hydroxide ions can be provided to help open the Si-O-Si framework in the glass structure.

[0057] When ammonia is used as the base, its weight in the alkaline etching solution is NH 3 The present invention is used to measure NH 3 The mass percentage concentration of NH is not particularly limited. 3 The mass percentage concentration is 25~28%.

[0058] In a specific embodiment, the ion chelator includes one or more of ethylenediaminetetraacetic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylphosphonic acid, and ethylenediaminetetramethylenephosphonic acid. When the above ion chelator is used, the escaped divalent cations can be captured to accelerate the etching reaction. When the ion chelator is less, the etching reaction is slow, and the micro-nano structure cannot be obtained in a shorter time and at a lower temperature, thereby affecting the hydrophobicity; when the ion chelator is more, the etching reaction is accelerated, which may cause local uneven etching, thereby reducing the transmittance; therefore, when the ratio of alkali to ion chelator is within the above range, the etching degree can be controlled within a reasonable range, thereby controlling the microstructure of the glass surface, thereby affecting the transmittance and hydrophobicity of the glass.

[0059] In a specific embodiment, the aluminate includes sodium aluminate and / or potassium aluminate. On the one hand, the aluminate is alkaline in hydrolysis, providing a large amount of hydroxide ions to the solution, which helps to open the Si-O-Si framework in the glass structure; on the other hand, after the Si-O-Si framework of the glass is opened, the aluminate can react with the free Al in the glass. 3+ Double hydrolysis reaction occurs, namely Al 3+ +3AlO 2- +6H 2 O=4Al(OH) 3 ↓, which can further accelerate the etching reaction.

[0060] In a specific embodiment, the weight percentage of aluminate to alkali is less than or equal to 10%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. When the weight percentage of aluminate to alkali is within the above range, Al(OH) 3 The amount of precipitation produced, avoiding Al(OH) 3 The precipitation adheres to the glass surface and affects the transmittance of the glass.

[0061] In a specific embodiment, step (1) specifically comprises: immersing the glass in an alkaline etching solution, etching at 80-100°C for 10-28 hours, with the glass being perpendicular to the bottom of the etching reaction device. The etching temperature may be 80°C, 85°C, 90°C, 95°C or 100°C, and the etching time may be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h or 28h.

[0062] The present invention does not specifically limit the etching reaction equipment. For example, the etching reaction equipment may be a polytetrafluoroethylene reactor.

[0063] When the glass is perpendicular to the bottom of the etching reaction device, it can be prevented that the precipitates generated during the etching reaction process adhere to the glass, thereby affecting the transmittance of the glass.

[0064] In a specific embodiment, step (2) specifically comprises: evenly spreading the inorganic salt on the micro-nano structure, and treating at 500-600° C. for 1-3 hours, for example, 1 hour, 2 hours or 3 hours. The present invention does not limit the thickness of the inorganic salt, which is based on the fact that the glass cannot be seen by the naked eye, and the thickness is preferably 1 mm.

[0065] The surface structure of the glass after treatment with inorganic salts is an irregular sponge-like structure, and the skeleton is composed of 10-20 nm nanoparticles.

[0066] Specifically, in step (2), the inorganic salts are mixed uniformly and then ground, and the micro-nano structure is treated at 500-600° C., for example, 500° C., 520° C., 540° C., 560° C., 580° C. or 600° C. to obtain a nanostructure.

[0067] The present invention does not impose any special restrictions on the grinding method and grinding time. For example, manual grinding or mechanical grinding can be performed, and it is only necessary to fully and evenly mix the inorganic salts. The grinding time is 10 to 60 minutes, preferably 20 to 30 minutes.

[0068] The present invention does not impose any particular limitation on the source of the inorganic salt, and the inorganic salt may be purchased from commercial products or prepared by conventional methods.

[0069] In a specific embodiment, the inorganic salt includes nitrate and chloride. The melting point of nitrate is about 350°C, and the melting point of chloride is about 800°C. At a treatment temperature of 500-600°C, nitrate can be melted, and the molten nitrate can exchange with the free sodium and potassium in the glass, which can reshape the surface morphology of the glass, that is, the molten nitrate forms microscopic pits on the surface of the glass, further improving the surface roughness and porosity of the glass. Chloride does not melt at a treatment temperature of 500-600°C, and plays a local protective role to prevent the molten nitrate from forming large pits on the surface of the glass. In addition, nitrate and chloride are both soluble in water and can be washed with clean water to prevent inorganic salts from remaining on the surface of the glass and affecting the transmittance and hydrophobicity.

[0070] It should be noted that other inorganic salts with a melting point below 600°C can be used to replace nitrates, and other inorganic salts with a melting point above 600°C can be used to replace chlorides. For example, fluoride salts can be used to replace chloride salts. It is not recommended to use carbonates instead of chloride salts because carbonates are alkaline and can react with glass at high temperatures, such as Na 2 CO 3 +SiO 2 =Na 2SiO 3 +CO 2 , Na 2 SiO 3 It cannot be dissolved in water, which will greatly reduce the transmittance of the glass surface.

[0071] In a specific embodiment, the weight ratio of the nitrate to the chloride is 1: 1. When the weight ratio of the nitrate to the chloride is 1: 1, uniform microscopic pits can be formed on the glass surface.

[0072] In a specific embodiment, the nitrate salt comprises potassium nitrate and / or sodium nitrate, and the chloride salt comprises sodium chloride and / or potassium chloride.

[0073] Specifically, in step (3), the present invention does not specifically limit the coating method of the low surface energy material. For example, the low surface energy material can be coated on the nanostructure by dip coating or evaporation.

[0074] When the dipping method is used, the glass treated with inorganic salt can be immersed in the dipping solution for 10 to 18 hours, and then the dipping glass is taken out of the dipping solution and placed in a blast drying oven for baking at 150°C for 30 minutes. The weight ratio of the diluent to the low surface energy substance in the dipping solution is 1:1.

[0075] The present invention does not impose any particular limitation on the diluent. For example, the diluent may include one or more of ethanol, isopropanol or acetone.

[0076] When the evaporation method is used, 0.5 mL of low surface energy material is dripped into the polytetrafluoroethylene reactor lining, and then the entire piece of glass treated with inorganic salt is placed into the polytetrafluoroethylene reactor lining. The reactor is then sealed and placed in an oven for reaction at 120°C for 2 to 4 hours. After the reaction is completed, the glass is taken out.

[0077] In a specific embodiment, the low surface energy material includes one or more of perfluoropolyether siloxane, fluorosilane and oligosiloxane. The low surface energy material can be used to improve the hydrophobicity of glass.

[0078] The glass of the present invention may be soda-lime glass.

[0079] Hereinafter, the preparation method of the highly transparent hydrophobic glass of the present invention is described in detail through specific examples.

[0080] Example 1

[0081] (1) Weigh the reagents according to the weight ratio of deionized water: sodium bicarbonate, sodium triphosphate, ethylenediaminetetraacetic acid and potassium aluminate in 120:5:2:1.05:0.5, mix and stir evenly to form a clear solution, which is the alkaline etching solution. Place ordinary soda-lime glass vertically into the lining of a polytetrafluoroethylene reactor, then pour the alkaline etching solution into it until the alkaline etching solution completely covers the glass, then place the reactor lining into a stainless steel reactor, and finally tighten the reactor nut to seal it. The sealed reactor is placed in a heating device at 90°C for 24 hours to obtain etched glass.

[0082] (2) Mix sodium nitrate and sodium chloride in a weight ratio of 1:1 and grind them in a mortar for 20 minutes. Sprinkle the ground inorganic salt evenly on the etched glass surface to a thickness of about 1 mm. Place the glass covered with molten salt in a muffle furnace and treat it at 600°C for 1 hour. After the treatment, dissolve the inorganic salt in deionized water and clean it.

[0083] (3) Place the glass after the inorganic salt treatment into the polytetrafluoroethylene reactor liner, add 0.5 mL of perfluoropolyether siloxane to the liner, then place the reactor liner into the stainless steel reactor, and finally tighten the reactor nut to seal. The sealed reactor is placed in a heating device and heated at 120°C for 2 hours.

[0084] Example 2

[0085] (1) Weigh the reagents according to the weight ratio of deionized water, sodium hydroxide, potassium hydroxide, ethylenediaminetetramethylenephosphonic acid and sodium aluminate in 100:3:2:1.05:0.25, mix and stir evenly to form a clear solution, which is the alkaline etching solution. Place ordinary soda-lime glass vertically into the lining of a polytetrafluoroethylene reactor, then pour the alkaline etching solution into it until the alkaline etching solution completely covers the glass, then place the reactor lining into a stainless steel reactor, and finally tighten the reactor nut to seal it. The sealed reactor is placed in a heating device at 90°C for 24 hours to obtain etched glass.

[0086] (2) Mix potassium nitrate and sodium chloride in a weight ratio of 1:1 and grind them in a mortar for 20 minutes. Sprinkle the ground inorganic salt evenly on the etched glass surface to a thickness of about 1 mm. Place the glass covered with molten salt in a muffle furnace and treat it at 550°C for 2 hours. After the treatment, dissolve the inorganic salt in deionized water and clean it.

[0087] (3) The glass treated with inorganic salts was immersed in the dipping solution for 10 hours, and then placed in a forced air drying oven and baked at 150° C. for 30 minutes. The weight ratio of ethanol to perfluoropolyether siloxane in the dipping solution was 1:1.

[0088] Example 3

[0089] The method for preparing highly transparent hydrophobic glass in Example 3 is substantially the same as that in Example 1, except that in step (1) of Example 3, ammonia water is used to etch the glass. The weight ratio of deionized water, ammonia water, ethylenediaminetetraacetic acid and potassium aluminate is 100:25:1.05:0.5. 3 The mass percentage concentration is 25%, that is, 25 parts of ammonia water contain 6.25 parts of NH 3 .

[0090] Example 4

[0091] (1) Deionized water, sodium pyrophosphate, 1-hydroxyethylidene-1,1-diphosphonic acid and sodium aluminate are weighed in a weight ratio of 100:3:1.05:0.5, mixed and stirred evenly to form a clear solution, which is the alkaline etching solution. Among them, the mass percentage of sodium metaphosphate and sodium pyrophosphate is 16.7%. Place ordinary soda-lime glass vertically into the lining of a polytetrafluoroethylene reactor, then pour the alkaline etching solution until the alkaline etching solution completely covers the glass, then place the reactor lining into a stainless steel reactor, and finally tighten the reactor nut to seal. The sealed reactor is placed in a heating device at 90°C for 24 hours to obtain etched glass.

[0092] (2) Mix potassium nitrate and sodium chloride in a weight ratio of 1:1 and grind them in a mortar for 20 minutes. Sprinkle the ground inorganic salt evenly on the etched glass surface with a thickness of about 1 mm. Put the glass covered with molten salt into a muffle furnace and treat it at 500℃ for 3 hours. After the treatment, dissolve the inorganic salt in deionized water and clean it.

[0093] (3) The glass treated with inorganic salts was immersed in the dipping solution for 10 hours, and then placed in a forced air drying oven and baked at 150° C. for 30 minutes. The weight ratio of ethanol to perfluoropolyether siloxane in the dipping solution was 1:1.

[0094] Comparative Example 1

[0095] The difference from Example 1 is that in step (1), the weight ratio of deionized water, sodium bicarbonate, sodium triphosphate, ethylenediaminetetraacetic acid and potassium aluminate is 100:6:3:0.2:2.

[0096] Comparative Example 2

[0097] The difference from Example 1 is that in step (2), no inorganic salt is used, and the etched glass is directly placed in a muffle furnace and treated at 600° C. for 1 hour.

[0098] Test example

[0099] 1. The surface structures of the glass before treatment, the glass after etching, and the glass after etching and treatment with inorganic salt in Example 1 were observed by electron scanning electron microscope (SEM).

[0100] like Figure 3 As shown in the figure, the untreated glass surface is smooth and flat, and the surface is covered with nanoparticles of about 10 nm. Figure 4 As shown in the figure, the surface structure of the etched glass is relatively dense, the grain size is 80~100 nm, there are certain gaps between the grains, and the porosity is about 10%. Figure 5 As shown in the figure, the surface structure of the glass after etching and treatment with inorganic salts is an irregular sponge-like structure. The skeleton is composed of 10-20 nm nanoparticles, with many pores with diameters of 50-100 nm distributed in the middle, and the porosity is increased to 40~50%.

[0101] 2. The atomic percentage of each element on the glass surface after etching in the embodiment and the comparative example was measured by an energy spectrometer. The results are shown in Tables 1 and Figure 6 .

[0102] from Figure 6 (b) and Figure 6 (c) It can be seen that the distribution of Ca and Mg elements is uneven, and their concentrations gradually decrease from the inside (unetched glass surface) to the outside (etched surface). The gradual change of the element density of the etching layer may bring about a gradual change in the refractive index of the etching layer, thereby reducing the reflectivity of light at the air / glass interface. Since the transmittance of glass = 1-reflectivity-absorption, the gradual change of the element density of the etching layer can increase the transmittance of the glass.

[0103] 3. Test the transmittance of the glass using a UV-Vis-IR-Vis spectrophotometer. Figure 7 and Table 1.

[0104] 4. Test the water contact angle of the glass using a water contact angle meter. The results are shown in Figure 8 and Table 1. The droplet size was 10 μL.

[0105] 5. The sliding angle of the glass was tested by a water contact angle measuring instrument with a tilting stage, and the results are shown in Table 1. The size of the water droplet was 10 μL.

[0106] 6. Test the self-cleaning ability of the glass through the water spray experiment. The results are shown in Fig. 9 and Table 1.

[0107] Table 1

[0108]

[0109] From Table 1, we can see that:

[0110] The transmittance of the glass prepared by the preparation method of the present invention reaches more than 95%, and the water contact angle reaches more than 140°. It can be seen that the method of the present application can improve the transmittance of the glass, and maintain the hydrophobicity of the glass while improving the transmittance. In addition, no highly corrosive acid and high-cost equipment are used in the reaction process, which is environmentally friendly and low-cost.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing highly transparent hydrophobic glass, characterized in that: The following steps are involved: (1) Etching micro-nano structures on the glass surface using alkaline etching solution; (2) treating the micro-nano structure at 500-600° C. with an inorganic salt to obtain a nanostructure; (3) Coating a low surface energy material on the nanostructure to obtain a highly transparent hydrophobic glass.

2. The method according to claim 1, characterized in that Taking the number of atoms of silicon, oxygen, sodium, aluminum, potassium, tin, magnesium and calcium as the total atomic amount, in the micro-nano structure, the atomic percentage of magnesium in the total atomic amount is 0.1-0.2%, and the atomic percentage of calcium in the total atomic amount is 0.1-0.3%.

3. The method according to claim 1 or 2, characterized in that: The alkaline etching solution comprises: 3-7 parts by weight of alkali, 0.5-1.5 parts by weight of ion chelating agent, 0.2-0.5 parts by weight of aluminate, and 80-120 parts by weight of deionized water.

4. The method according to claim 3, characterized in that The alkali includes one or more of sodium bicarbonate, sodium triphosphate, sodium hydroxide, potassium hydroxide, ammonia water, sodium pyrophosphate, and sodium carbonate.

5. The method according to claim 3 or 4, characterized in that: The ion chelating agent includes one or more of ethylenediaminetetraacetic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylphosphonic acid, and ethylenediaminetetramethylenephosphonic acid.

6. The method according to any one of claims 3 to 5, characterized in that: The aluminate includes sodium aluminate and / or potassium aluminate.

7. The method according to any one of claims 3 to 6, characterized in that: The weight percentage of the aluminate to the alkali is less than or equal to 10%.

8. The method according to any one of claims 1 to 7, characterized in that: The step (1) specifically comprises: immersing the glass in the alkaline etching solution, etching at 80-100° C. for 10-28 hours, with the glass being perpendicular to the bottom of the etching reaction device; And / or, the step (2) specifically comprises: spreading the inorganic salt evenly on the micro-nano structure, and treating at 500-600° C. for 1-3 hours.

9. The method according to any one of claims 1 to 8, characterized in that: The inorganic salts include nitrates and chlorides; Preferably, the weight ratio of the nitrate to the chloride is 1:1; Preferably, the nitrate comprises potassium nitrate and / or sodium nitrate, and the chloride comprises sodium chloride and / or potassium chloride.

10. The method according to any one of claims 1 to 9, characterized in that: The low surface energy material comprises one or more of perfluoropolyether siloxane, fluorosilane and oligosiloxane; And / or, the glass is soda-lime glass.

Citation Information

Patent Citations

  • Method for preparing glass surface super-hydrophobic membrane

    CN107365088A

  • Super-hydrophobic transparent glass and preparation method thereof

    CN107500554A

Cited By

  • High-transmittance super-hydrophobic wear-resistant photovoltaic glass and preparation method thereof

    CN122502109A